2000
DOI: 10.1117/12.390311
|View full text |Cite
|
Sign up to set email alerts
|

<title>Principles, limitations, and performance of multiconjugate adaptive optics</title>

Abstract: Multi-Conjugate Adaptive Optics (MCAO) holds the promise of moderate to large adaptively compensated field of view with uniform image quality. This paper is a first effort to analyse the fundamental limitations of such systems, and that are mainly related to the finite number of deformable mirrors and guide stars. We demonstrate that the ultimate limitation is due to the vertical discretization of the correction. This effect becomes more severe quite rapidly with increasing compensated field of view or decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 1 publication
(1 reference statement)
1
73
0
1
Order By: Relevance
“…We note that, as pointed out by Le Louarn et al (2000), the value of θ D,hmax and G could change if we consider a different definition of the FOV θ. We finally note that, in a more recent papers (Rigault et al 2000), the authors observed that a field of view of the order of those calculated in our paper should require a too large number of DMs to correct the perturbed wavefront. This is due to the fact that, the larger the FOV, the higher the number of the DMs necessary to keep the MCAO errors (generalized fitting and anisoplanetism errors) down.…”
Section: Cmentioning
confidence: 54%
“…We note that, as pointed out by Le Louarn et al (2000), the value of θ D,hmax and G could change if we consider a different definition of the FOV θ. We finally note that, in a more recent papers (Rigault et al 2000), the authors observed that a field of view of the order of those calculated in our paper should require a too large number of DMs to correct the perturbed wavefront. This is due to the fact that, the larger the FOV, the higher the number of the DMs necessary to keep the MCAO errors (generalized fitting and anisoplanetism errors) down.…”
Section: Cmentioning
confidence: 54%
“…In this way the corrected field of view (FoV) is wider than the small isoplanatic patch of few arcsecond typically achievable at visible and nearinfrared wavelengths by means of classical single conjugated AO systems [2]. MAORY is requested to provide corrected images over a FoV up to 2arcminutes diameter at near-infrared wavelengths from I to H band and to operate at zenith angles up to 60…”
Section: Introductionmentioning
confidence: 99%
“…The field of view in this sensor is 35 . The high-altitude DMs were conjugated to about 3 and 8 km beyond the telescope on the line of sight, such that they almost continuously cover the first 11 km (see Rigaut et al 2000). The wavefront sensor field of view was subdivided into 3 × 3 guideregions in which digital image correlation was performed to estimate wavefront slopes in the Shack-Hartmann subapertures; this is the standard method used for solar Shack-Hartmann sensors (Rimmele & Marino 2011).…”
Section: Clear Experiments In July 2016mentioning
confidence: 99%
“…Supplemental wavefront sensors must be deployed to probe the optical aberrations over the targeted field of view in order to steer the DMs. This concept is known as multiconjugate adaptive optics (MCAO;Dicke 1975;Beckers 1987Beckers , 1988Ellerbroek 1994;Rigaut et al 2000;Fusco et al 2001;Tokovinin et al 2001). Stellar observations with MCAO were first carried out by the MCAO Demonstrator MAD at the Unit Telescope 3 of the Very Large Telescope (Marchetti et al 2007).…”
Section: Introductionmentioning
confidence: 99%